One Dollar CEOs - Loureiro, Gilberto (2020)
We study the impact of $1 CEO salaries on firm performance and CEO total compensation. We find that, on average, $1 CEO firms earn higher total compensation and lower stock market returns relative to their peers after the adoption of $1 salaries. The effect on total compensation is mitigated if the $1 CEO firm is undergoing restructuring or the CEO is entrenched and aggravated if the CEO is overconfident. The stock market underperformance especially affects firms not under a restructuring process and firms with entrenched or overconfident CEOs.